2019
DOI: 10.1111/os.12536
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the Long Head of the Biceps Tendon Concomitant with Rotator Cuff Tears: Tenotomy or Subpectoral Mini‐open Tenodesis? A Comparative Short to Mid‐term Follow‐up Study

Abstract: ObjectiveTo compare the clinical and radiological outcomes of patients who underwent rotator cuff repair (RCR) concomitant with long head of the biceps tendon (LHBT) tenotomy or subpectoral mini‐open tenodesis.MethodsProspectively collected data was reviewed on 154 patients, who underwent a LHBT procedure (tenotomy or tenodesis) concomitant with RCR between January 2010 and January 2017. The exclusion criteria were irreparable massive rotator cuff tear, rotator cuff partial tear, subscapular tendon tear, gleno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
10
0
2
Order By: Relevance
“…In addition, recent clinical studies also yield opposite results in terms of constant score. [ 24 , 34 ] In the current study, the pooled Constant scores are consistent with the studies by Na et al [ 14 ] and Shang et al [ 13 ] However, even though the result for Constant score was statistically reliable after sensitivity analysis, the TSA indicated that the meta-analysis may obtained false-positive conclusion. As shown in Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, recent clinical studies also yield opposite results in terms of constant score. [ 24 , 34 ] In the current study, the pooled Constant scores are consistent with the studies by Na et al [ 14 ] and Shang et al [ 13 ] However, even though the result for Constant score was statistically reliable after sensitivity analysis, the TSA indicated that the meta-analysis may obtained false-positive conclusion. As shown in Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Twenty-five studies reporting on 2,191 participants were included in this meta-analysis. 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 Of these, 1,003 patients were treated with tenodesis (46%), and 1,188 were treated with tenotomy (54%). There were 8 level I studies, 5 level II studies and 12 level III studies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the surgical technique used was not standardized, and included different tenodesis sites and use of an anchor for the LHBT independently or in association with rotator cuff repair. Most comparative studies have evaluated tenodesis with anchors, 7 , 19 22 , 25 and few have evaluated use of interference screws. 17 , 24 …”
Section: Discussionmentioning
confidence: 99%